Sobre rigidez de métricas quasi-Einstein - Borges, Laena Furtado (2017)
In this work, we will present some concepts of quasi-Einstein metrics. From this, we will enunciate and demonstrate rigidity results for quasi-Einstein metrics until we have enough material to demonstrate a stiffness result for quasi-Einstein metrics of dimension two. Finally, we will give some concepts of Kähler metrics, prove a theorem and finally demonstrate a corollary that connects the main theorem of our work with Kähler metrics.